2015
DOI: 10.1016/j.ajo.2015.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging of Central Retinal Disease Progression in a 2-Year Mean Follow-up of Retinitis Pigmentosa

Abstract: Purpose To determine the rate of progression and optimal follow up time in patients with advanced stage retinitis pigmentosa (RP) comparing the use of fundus autofluorescence imaging and spectral domain optical coherence tomography. Design Retrospective analysis of progression rate. Methods Longitudinal imaging follow up in 71 patients with retinitis pigmentosa was studied using the main outcome measurements of hyperautofluoresent ring horizontal diameter and vertical diameter along with ellipsoid zone lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
72
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 56 publications
14
72
3
Order By: Relevance
“…In general, the mean annual rate of progression is our dataset is comparable with previous studies: the EZ line width reduction was 4.16% per year in accordance with 4.9–10.9% [34, 36, 38] reported in published literature. Similarly to published data, we observed that the progression rate of the EZ band atrophy decreases when the margins of the atrophic retina approach the foveal region [34, 36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the mean annual rate of progression is our dataset is comparable with previous studies: the EZ line width reduction was 4.16% per year in accordance with 4.9–10.9% [34, 36, 38] reported in published literature. Similarly to published data, we observed that the progression rate of the EZ band atrophy decreases when the margins of the atrophic retina approach the foveal region [34, 36].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to published data, we observed that the progression rate of the EZ band atrophy decreases when the margins of the atrophic retina approach the foveal region [34, 36]. …”
Section: Discussionsupporting
confidence: 86%
“…Sujirakul et al 15 observed a significantly lower mean rate of structural progression in patients with RP who had a smaller preserved EZ band, which suggests that the progression rate decreases as the disease approaches the fovea. We observed a tendency toward higher variability in grading of the EZ area in eyes with a smaller preserved EZ area in our study.…”
Section: Discussionmentioning
confidence: 98%
“…14 With time the diameter of the ring progressively constricts. 5 Outside the SW-AF ring, photoreceptor cell degeneration is evidenced by loss of the ellipsoid zone (EZ) and external limiting membrane (ELM) and thinning or absence of the reflectivity layer corresponding to outer nuclear layer (ONL) in SD-OCT scans. 6,7 This thinning of photoreceptor-attributable reflectivity layers in SD-OCT scans also corresponds to a reduction in multi-focal ERG amplitudes.…”
mentioning
confidence: 99%